Effort optimisation in artisanal fisheries with multiple management objectives, collective quotas and heterogeneous fleets*. (21st November 2012) - Castillo, Carlos; Dresdner, Jorge
Abstract : In this study, we analyse effort optimisation in common rights‐based joint‐stock artisanal fisheries when several objectives are pursued by the authorities and the fleets are heterogeneous. The purpose is to discuss policy options available to the authorities and their implications in terms of trade‐offs between goals. We apply a multi‐objective programming model to the sardine and anchovy artisanal fisheries in central southern Chile. The results suggest that the regulatory system generates inefficient solutions for profit and employment maximisation goals. Moreover, the fleet structure of the artisanal organisations is central for the outcomes obtained by different policy simulations. To improve effort assignment, the authorities should seek to increase flexibility in the system.